1999
DOI: 10.1074/jbc.274.53.37965
|View full text |Cite
|
Sign up to set email alerts
|

Activation of the MAPK Signal Cascade by the Neural Cell Adhesion Molecule L1 Requires L1 Internalization

Abstract: L1-mediated axon growth involves intracellular sig

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

12
171
1

Year Published

2000
2000
2024
2024

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 168 publications
(186 citation statements)
references
References 85 publications
12
171
1
Order By: Relevance
“…Maness and colleagues have determined that dynamin-mediated endocytosis of the neural cell adhesion molecule L1 following homotypic interaction or antibody-induced clustering is essential for ERK activation and neurite outgrowth [151]. L1 dependent activation of ERK can be blocked by preventing L1 endocytosis and internalized L1 colocalizes with ERK [152]. While L1 is not an integrin, it functionally interacts with β 1 integrins to potentiate neuronal migration toward ECM through endocytosis and MAP kinase signaling [153].…”
Section: Erk and Microtubule And Motor Dynamicsmentioning
confidence: 99%
“…Maness and colleagues have determined that dynamin-mediated endocytosis of the neural cell adhesion molecule L1 following homotypic interaction or antibody-induced clustering is essential for ERK activation and neurite outgrowth [151]. L1 dependent activation of ERK can be blocked by preventing L1 endocytosis and internalized L1 colocalizes with ERK [152]. While L1 is not an integrin, it functionally interacts with β 1 integrins to potentiate neuronal migration toward ECM through endocytosis and MAP kinase signaling [153].…”
Section: Erk and Microtubule And Motor Dynamicsmentioning
confidence: 99%
“…However, previous work has shown that components of the MAP kinase pathway, ERK and p90rsk, can phosphorylate directly serines located in the cytoplasmic domain of L1-CAM (Schaefer et al, 1999). To investigate whether the MAP kinase signaling cascade is required for the phosphorylation of the FIGQY sequence, we examined the effect of two inhibitors of the MAP kinase kinase MEK1/2, PD98059 and U0126 (English and Cobb, 2002) on the BRET ratio of the L1-BRET construct transfected in HEK-293 cells.…”
Section: The Map Kinase Pathway Regulates the Tyrosine Phosphorylatiomentioning
confidence: 99%
“…Although we have focused on the tyrosine phosphorylation of the L1-CAM cytoplasmic tail at the FIGQY motif that mediates ankyrin binding, MAP kinase signaling has also been implicated in L1-CAM function as a receptor for nerve growth-promoting signals (Schaefer et al, 1999;Loers et al, 2005). Additionally, the MAP kinase pathway has been implicated in L1-mediated neuroprotection (Loers et al, 2005).…”
Section: Map Kinase Pathway Activity and The Regulation Of L1-cam-medmentioning
confidence: 99%
“…The 210-kDa form may also be full-length L1, but with immature glycosylation. The immaturity of the glycosylation may interfere with the immunoreactivity with L1CD and L1ED, since both these antibodies were raised against proteins produced either as recombinants in bacteria (Schaefer et al, 1999) or from transfected COS7 cells (Fransen et al, 1998) and thus expected to have different posttranslational modifications. These full-length transmembrane forms of L1 may be found in CSF as part of membrane vesicles which are released in response to different signals .…”
Section: Discussionmentioning
confidence: 99%
“…Length of storage at −80°C had no effect on banding pattern or density. Immunoblots were developed using primary antibodies of rabbit polyclonal antibodies to both full-length human L1 (L1FL) (Wong et al, 1995) and L1 cytoplasmic domain (L1CD) (Schaefer et al, 1999) and mouse monoclonal antibody to a human L1-Fc chimera containing the extracellular domain of L1 (L1ED) (all antibodies kindly provided by Dr. Vance Lemmon). Secondary antibodies were goat anti-rabbit or goat anti-mouse conjugated to horseradish peroxidase obtained from Jackson Laboratories and developed using epichemiluminescence.…”
Section: Methodsmentioning
confidence: 99%